Rancang Bangun Tungku Peleburan Logam Non Ferro Dengan Sistem Induksi Berkapasitas 5 Kg - Susilowati, Sri Endah; Sumardiyanto, D (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
A design for a single-phase electric induction furnace has been carried out to smelt non-ferrous metals with a capacity of 5 kg. Electric induction furnaces are the most ideal melters as long as the composition of the charge is controlled, including its reliability in the action of stirring the melt, making the homogeneity of the chemical composition of the casting better. The resulting gas and smoke emissions are very low as long as the incoming materials are physically clean. The furnace is designed by considering the voltage and electric current system to reach the melting temperature. The design of the furnace is in the form of a cylindrical cup with an inner diameter of 6.7 cm and a height of 15 cm. The power supply provided is 1.32 KVA and 2 KVA, the energy required for smelting is 96 kJ. The test results obtained by induction melting at a crucible load with a capacity of 5 kg made from graphite showed that the maximum temperature increase was ΔT = 575 oC and the amount of heat Q = 342.9 kJ.